45. Salvage re-irradiation for local failure of prostate cancer after curative radiotherapy: Dosimetric and radiobiological modelling of rectal toxicity. (December 2017) - Dipasquale, G.; Zilli, T.; Fiorino, C.; Rouzaud, M.; Miralbell, R.
Abstract : Introduction: To assess the impact of radiation dose and clinical parameters on rectal toxicity following salvage external beam radiation therapy (EBRT) with or without a brachytherapy (BT) boost for exclusive local failure after primary-EBRT for prostate cancer. Methods: Fourteen patients with no residual toxicity after primary EBRT ( ± BT) were re-irradiated after a median time interval of 6.1 years (4.7–10.2). The median NTD2Gy was 74 Gy (66–98.4) at primary-RT and 85.1 Gy (70–93.4) at re-irradiation. Rectal dose volume histograms of both treatments (converted to NTD2Gy) and the corresponding normal-tissue-complication-probability (NTCP) values for gastro-intestinal (GI) toxicity were calculated. Results: The 5-year Grade ⩾3 GI toxicity-free survival rate was 57.1 ± 13.1%. Five patients developed Grade 4 GI toxicity. Rectal V70Gy and the maximum dose to 1 cc of rectum at primary EBRT were both predictive for Grade ⩾3 GI toxicity; 12.2% vs. 3.8%, p = .042 and 72.2 Gy vs. 66.8 Gy, p = .0027, respectively. When adding primary-RT and re-irradiation plans, the median maximum dose to 1 cc of rectum was 139.8 Gy (126.7–147.8) vs. 125.9 Gy (99.1–133.1) (p = .0063) for Grade ⩾3 and Grade ⩽2 GI toxicity groups. Higher NTCP values at primary-RT were predictive for Grade ⩾3 toxicity (p < .05). Conclusions: A higher rectal NTCP value, even in the absence of high-grade late-toxicity after primary-RT, is correlated with an increased risk of severe rectal side-effects after salvage re-irradiation. Rectum doses greater than 70 Gy at primary-RT, and NTCP values of more than 10%, might predict for grade ⩾3 rectal toxicity at re-irradiation, with a possible threshold for total rectum dose of around 130 Gy.